High performance supercapattery incorporating ternary nanocomposite of multiwalled carbon nanotubes decorated with Co 3 O 4 nanograins and silver nanoparticles as electrode material - Iqbal, Javed; Numan, Arshid *; Rafique, Saqib; Jafer, Rashida; Mohamad, Sharifah; Ramesh, K.; Ramesh, S. (Elsevier, 2018)
Cobalt oxide (Co3O4) nanograins were in situ grown on chemically activated multiwall carbon nanotubes (MWCNT) and anchored with silver (Ag) nanoparticles to form a ternary nanocomposite (MWCNT-Co3O4-Ag) by simple single step hydrothermal route. The structural crystallinity and successful synthesis of MWCNT-Co3O4-Ag nanocomposite were confirmed by X-ray diffraction. The surface morphology, homogeneity, specific surface area and crystallinity were evaluated by field emission scanning electron microscopy, energy dispersive X-ray spectroscopy with mapping, Brunauer Emmett Teller and X-ray diffraction analysis, respectively. Cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy were conducted in 1 M KOH electrolyte to analyze electrochemical performance of the prepared samples as an electrode material for supercapattery. The MWCNT-Co3O4-Ag nanocomposite witnessed the maximum specific capacity of 83.88 Cg-1 at 0.6 Ag-1 which is substantially higher than MWCNT-Co3O4 (55.33 Cg-1) and Co3O4 nanograins (39.24 Cg-1) in standard three electrode cell system. The remarkable electrochemical performance of ternary nanocomposite was associated with the effect of Co3O4 nanograins, conductive platform provided by the MWCNT and synergistic effect of Ag nanoparticles. The supercapattery devices were fabricated in a configuration of MWCNT-Co3O4-Ag//activated carbon. The hybrid device was capable to operate in stable potential window of 1.5 V even at higher scan rates. It was observed that the fabricated supercapattery showed an energy density of 16.5 Whkg−1 with power density of 297.5 Wkg-1 at current density of 0.2 Ag-1. Additionally, life cycle test revealed that supercapattery was highly stable and lost only 6.4% of its initial capacity after 3000 cycles.